Investment and Labor Absorption on Poverty Levels through the Dynamics of Economic Growth in West Papua - Hasbiah; Nur Imam Saifuloh; Deni Anggreani Sutomo; Erwin Horas; Sri Prilmayanti Awaluddin (Institut Bisnis dan Informatika Kesatuan, 2025)
Poverty in Indonesia is not only caused by low income but also by limited access to education, health, and basic services. West Papua has a high poverty rate compared to the national average, suggesting that economic growth and investment have not been effective in reducing it. This study aims to analyze the impact of investment and labor absorption on poverty through economic growth in West Papua. The research method used BPS secondary data from 13 districts/cities during 2011–2023, analyzed with Eviews 13 and Microsoft Excel. Panel data regression with Chow, Hausman, and Lagrange Multiplier tests is used to determine the best model, as well as regression tests, R², and F-tests to measure relationships between variables. The results showed that investment and GDP growth significantly reduced poverty, while labor absorption had no significant effect. The impact of investment depends on the sector and the distribution of benefits, while economic growth has the greatest influence on poverty reduction. Therefore, policies must direct investment to labor-intensive sectors, improve the quality of the workforce, and ensure inclusive economic growth so that the benefits are evenly distributed throughout society.